السياسة الخارجية الرّوسية في الشرق الأوسط بعد الحرب الباردة - خليل, فادي; حسن, سمير; الدليمي, مصعب (Latakia University Journal - Economic and Legal Sciences Series, 2016)
أصبحت روسيا بعد انهيار الاتحاد السوفييتي وانتهاء الحرب الباردة، الوريث الشرعي والقانوني للاتحاد السوفييتي، وورثت عنه المقعد الدائم في مجلس الأمن الدولي، ولتوافر مجموعة من عوامل القوةمثل المساحة الجغرافية والإمكانات الاقتصادية وعددالسكان والقدرات العسكرية بما فيها الترسانة الكبيرة من السلاح النووي، جعلت من روسيا واحدة من القوى الفاعلة على المستوى الدولي، لذلك فهي تحاول اليوم أن يكون لها دورٌ مهمّ في منطقة الشرق الأوسط، وتطمح أن تكون منافساً للولايات المتحدة الأمريكية في المنطقة، وخلال فترة حكم بوتين تجسدت السياسة الخارجية الروسية في منطقة الشرق الأوسط بمواقف ازدادت قوة مع تصاعد الأزمات الإقليمية، ولاحظنا ذلك في الموقف الروسي من الاحتلال الأمريكي للعراق، وكذلك موقفها من أحداث مايسمى "بالربيع العربي"، وهذا ما جعل دور روسيا يزداد أهمية مع تحقيق الاستقرار في منطقة الشرق الأوسط. After the collapse of the Soviet Union and the end of the cold war, Russia became the legitimate heir to the Soviet Union, and inherited his permanent seat in the UN Security Council, and the availability of a range of strengths such as geographicalarea and economic potential and population, and military capacity, including large nuclear arsenal, has made Russia one of the actors at the international level, so they are trying today to have an important role in the Middle East, and aspires to be a competitor for the United States in the region, during the reign of Putin'sreflected Russian foreign policy in the Middle East positions strengthened with regional crises, we noted that in the Russian stance of the US occupation of Iraq, as well as the position of the so-called "Arab spring", this has made the role of Russia is increasing the importance of achieving stability in the Middle East.